Electronic Development Of Problem Based Learning Learner Worksheet Based On Liveworksheet SDIT Al- Muthmainnah Jambi City - Bimbi Arini; Sri Yulia Sari; Tika Sari (PGMI IAIN Lhokseumawe, 2024)
Lack of variation in the use of supporting teaching materials used in the learning process of Natural and Social Sciences (IPAS), teaching materials available at school are still in the form of printed books, this causes the learning process to be less varied and less interesting, making students bored and bored during the learning process. The purpose of this study was to develop electronic problem-based learning worksheets based on liveworksheet SDIT Al-Muthmainnah Jambi City which is valid and effective. This type of research is development research (research and development) with a development model, namely the ADDIE model. ADDIE consists of five stages, namely: (1) Analyze (analysis), (2) Design (design), (3) Development (development), (4) Implementation (implementation), (5) Evaluation (evaluation). The results of the validity of the E-LKPD product obtained from the material expert validation results are 96% with a very valid category. The results of the analysis of the media expert validation obtained 98% with the category sanagt valid. The results of the analysis of the linguist validation were 80% with the valid category. Educators and students gave a positive response to the E-LKPD product developed with the percentage obtained from the educator's response questionnaire of 96% and students of 90%. This teaching material is effective for students as evidenced by the results of data obtained from the students' response questionnaire after using the E-LKPD product of 94% in the very effective category. From the results of these responses, it can be concluded that the electronic product of problem-based learning student worksheets based on liveworksheet is valid and effective for use in the IPAS learning process.